A note on the incidence of soilborne fungi in six crops used in rotation with potatoes - Celetti, M.J.; Johnson, H.; Platt, H.W. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1990)
The incidence of soilborne fungi was determined in tissue immediately below the soil line of clover (Trifolium hybridum and T. pratense), peas (Pisum sativum), soybean (Glycine max), ryegrass (Lolium multiflorum), barley (Hordeum vulgare), and winter wheat (Triticum aestivum) grown in rotation with potatoes (Solarium tuberosum). Legume crops had significantly higher incidence of Verticillium albo-atrum, Colletotrichum coccodes, and Fusarium solani than the gramineaceous crops. Peas had the highest incidence of V. albo-atrum and F. solani.C. coccodes was isolated more frequently from soybean than from clover, peas, ryegrass, barley, or winter wheat. Verticillium dahliae was isolated from all crops except clover. Gramineaceous crops had a significantly higher incidence of V. dahliae than legume crops. The incidence of Fusarium sambucinum was higher in soybeans than all other crops. Fusarium oxysporum was isolated most frequently from soybeans and barley. The highest incidence of Rhizoctonia solani was in clover, but it was also isolated more frequently from winter wheat and ryegrass than from soybean and barley.